The university extension as an agent for social transformation: a case study of the Community Library of Saramenha de Cima neighborhood - Ouro Preto/MG (Research, Society and Development, 2021)
Community libraries are social environments created by the community to promote access to information and leisure for the local population. These environments become important support points, reducing social inequalities and guaranteeing pedagogical and cultural development. In this context, in 2005, the Community Library of Saramenha de Cima was created, in the neighborhood of the same name in the city of Ouro Preto-MG, in a partnership between local groups and the Federal University of Ouro Preto (UFOP). The library promotes activities to encourage reading, workshops, tutoring and book lending, with the participation in the project's activities of university extension students from UFOP's undergraduate courses. This article assesses the impact of the Saramenha de Cima Community Library in improving the education and quality of life of the local population, through a survey of school performance data of participating children, analysis of the main points of transformation in the community and in personal development, and academic extension workers. The study highlighted how the project brought the feeling of pride and belonging to the local population, becoming a point of leisure, culture and, above all, educational development, with the neighborhood school achieving educational growth with the support of the library, obtaining superior results such as academic performance municipal, state and national. In addition, the project promotes a rapprochement between the community and the university, also ensuring a very important personal maturity to the participating extension workers, preparing academics, presenting related works and making them more human and better prepared for the future.